A vision for Water Resources Research. Issue 6 (3rd June 2017) - Clark, Martyn P.; Bahr, Jean A.; Bierkens, Marc F. P.; Cai, Ximing; Hogue, Terri S.; Luce, Charles H.; Lundquist, Jessica D.; Mackay, D. Scott; van Meerveld, H. J. (Ilja); Rajaram, Harihar; Sanchez‐Vila, Xavier; Troch, Peter A.
Abstract: Water Resources Research (WRR) continues to evolve as the team of international editors begins a new 4 year term of service. In this Editorial we summarize the importance of WRR in the hydrologic sciences, the challenges ahead, and the plans for the future of the journal. Key Points: Our primary goal as WRR Editors is to enhance the quality and impact of hydrologic science We will strive to ensure that WRR is regarded as the "journal of choice" for high‐quality interdisciplinary science The WRR Editorial board is committed to increasing the impact and visibility of WRR papers